Study on Customized Assisted Reproduction Enhancement (CARE) for Women with Extremely Poor Ovarian Reserve (EPOR) - Jan Tesarik (Emerging Trends in Disease and Health Research Vol. 9, 2022)
Anti-Müllerian hormone (AMH) levels in the blood and the number of ovarian antral follicles are commonly used to assess ovarian reserve. Because of a low response to ovarian stimulation, women with moderately compromised ovarian reserve (AMH levels between 0.2ng/ml and 1.1ng/ml) have a poor likelihood of conceiving a child through in vitro fertilization (IVF). However, research on forecasting the chances of women with severely low ovarian reserve (AMH \(≤\)0.2ng/ml) has produced mixed results. Many clinics throughout the world refuse to admit women with very low ovarian reserve (EPOR), claiming that their chances of success are nil. This study found that with customized assisted reproduction enhancement (CARE), this group of women can achieve a relatively high clinical pregnancy rate (23%) and delivery rate (18%). During the pre-stimulation phase, ovarian stimulation, embryological laboratory work, and patient follow-up after embryo transfer, the CARE protocol personalizes the patient’s care.